ANATOMICAL AND PHYSIOLOGICAL FEATURES OF THE RESPIRATORY TRACT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is intended to fully reveal the anatomical and physiological features of the respiratory tract, diseases of the respiratory tract and the solution of these diseases.